The effect of the US Financial Crisis on the Kenyan Equity market: A Sectoral Perspective - Contractor, Janisha Nitinchandra (2010)
This study analyzes the relationship between the Nairobi Stocj Exchange and the US equity market before and after the 2007 financial crisis. Furthermore, the analysis is carried out on a sector basis in order to examine the relationships between the US equity market and the four distinct sectors of the Kenyan economy; Finance and Investment, Industry and Allied, Commercial and Services and Agriculture. The dominant role of US market has been brought to light for decades. However this study concludes that other transmission channels had a greater impact on the Nairobi Stock Exchange as opposed to the US market. this study further shows that the crisis, the relationship between the Kenyan and US markets strengthen. Furthermore, this stronger relationship is also evident in the sector analysis. In the long term the tests depict that the Agricultural sector has a long term relationship with the US market. This brings to light the important role that the Agricultural sector still plays in Kenya in terms of export ties with the US. In the post-crisis period it is noted that out of the four sectors, the US market explains most the movements of the Finance and Investments Sector. It is evident that over the years the Finance and Investments sector of the economy has been growing and thus making the economy more vulnerable to international financial shocks. Therefore the study provides short term and long term recommendations to cushion this sector from importing future crises